2022
DOI: 10.3390/genes13030549
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HK2, PKM2, and PFKM Is Associated with Metastasis and Late Disease Onset in Breast Cancer Patients

Abstract: The reprogramming of energy metabolism is one of the hallmarks of cancer and is crucial for tumor progression. Altered aerobic glycolysis is a well-known characteristic of cancer cell metabolism. In the present study, the expression profiles of key metabolic genes (HK2, PFKM, and PKM2) were assessed in the breast cancer cohort of Pakistan using quantitative polymerase chain reaction (qPCR) and IHC. Expression patterns were correlated with molecular subtypes and clinical parameters in the patients. A significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A dynamic metabolic shift in the NPCs was also observed in our data in which, at higher doses of CBD (5 µM), a decrease in glycolysis and an increase in β-oxidation were favored, mainly from the early to the nal stages of metabolic pathways. Enzymes such as hexokinase and pyruvate kinase play an essential role in the glycolytic pathway as both enzymes are allosterically regulated, which means they can regulate glycolysis (Ishfaq et al 2022). Therefore, the decrease of HK2 and PKM2 expression observed in our study at higher concentrations of CBD can be interpreted as the allosteric regulation of both enzymes due to the lower presence of glucose.…”
Section: Discussionmentioning
confidence: 55%
“…A dynamic metabolic shift in the NPCs was also observed in our data in which, at higher doses of CBD (5 µM), a decrease in glycolysis and an increase in β-oxidation were favored, mainly from the early to the nal stages of metabolic pathways. Enzymes such as hexokinase and pyruvate kinase play an essential role in the glycolytic pathway as both enzymes are allosterically regulated, which means they can regulate glycolysis (Ishfaq et al 2022). Therefore, the decrease of HK2 and PKM2 expression observed in our study at higher concentrations of CBD can be interpreted as the allosteric regulation of both enzymes due to the lower presence of glucose.…”
Section: Discussionmentioning
confidence: 55%
“…In vitro study, we observed decreased protein levels and activities of HK1 and PKM1 in the HT22 cells injured by Ab 25-35 , which were increased after ICA treatment; while the expression and activity of PFKM1 were not significantly different in all groups of HT22 cells, which was slightly different from the results of vivo experiments. The disparity in PFKM1 protein and activity levels between in vivo and in vitro conditions may be attributed to the influence of factors such as exercise, diet (specifically high fructose intake), age, and disease on in vivo experiments [53][54][55], which are absent from in vitro studies. However, the exact mechanism is still not fully discovered and there are other possible reasons for the difference, all of which need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…HK2 is a hexokinase that participates in glycolysis and is essential for the Warburg effect. HK2 level increases in several types of human tumors, and this enzyme participates in the cell cycle process [ 34 36 ]. PDK1 phosphorylates the pyruvate dehydrogenase (PDH) E1α subunit to inactivate the PDH enzyme complex, and the PDH enzyme complex can then convert pyruvate into acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%